2016
DOI: 10.3854/crm.5.098.euphraticus.v1.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rafetus euphraticus (Daudin 1801) – Euphrates Softshell Turtle

Abstract: The Euphrates Softshell Turtle, Rafetus euphraticus (Family Trionychidae), is a medium-sized (maximum recorded carapace length 680 mm), freshwater turtle thought to be most closely related to the eastern Asian species Rafetus swinhoei. The species inhabits diverse habitats, including rivers, streams, ponds, lakes, reservoirs, marshlands, and artificial canals. It is found only in the Euphrates and Tigris rivers and their tributaries in Turkey, Syria, Iraq, and southwestern Iran. It occurs in relatively shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The construction of large dams on the Euphrates River strongly affected the water level fluctuations and decreased the temperature; thus, the growth of aquatic vegetation eliminated turtle basking spots while the rising water level submerged potential nesting sites (Gramentz, 1993; Taşkavak & Atatür, 1995; Taşkavak & Atatür, 1998). The construction of dams for many years has undoubtedly caused many potential habitats and nesting sites of R. euphraticus to be submerged, destroyed and fragmented (Taskavak et al, 2016). Reservoir sedimentation dramatically reduces the volume of sand that can be transported downstream, causing the progressive disappearance of river beaches and sandy islands.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The construction of large dams on the Euphrates River strongly affected the water level fluctuations and decreased the temperature; thus, the growth of aquatic vegetation eliminated turtle basking spots while the rising water level submerged potential nesting sites (Gramentz, 1993; Taşkavak & Atatür, 1995; Taşkavak & Atatür, 1998). The construction of dams for many years has undoubtedly caused many potential habitats and nesting sites of R. euphraticus to be submerged, destroyed and fragmented (Taskavak et al, 2016). Reservoir sedimentation dramatically reduces the volume of sand that can be transported downstream, causing the progressive disappearance of river beaches and sandy islands.…”
Section: Discussionmentioning
confidence: 99%
“…Based on published literature and field observations on preferred habitat types, we suggest that if these shorelines are transformed into vegetated shorelines in the years to come, suitable habitats for turtles are likely to increase. However, Taskavak et al (2016) stated that even if suitable substrates are found for basking and nesting in the recently constructed reservoir areas, fluctuations in the water level are likely to make survivorship of nests extremely low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations